Effect of Lactobacillus plantarum ZFM4 in Helicobacter pylori-infected C57BL/6 mice: prevention is better than cure - Yu, Ying-ying; Wu, Ling-yan; Sun, Xue; Gu, Qing; Zhou, Qing-qing (Frontiers in Cellular and Infection Microbiology, 2024)
Objectives This study was performed to explore the preventive and therapeutic effects of Lactobacillus plantarum ZFM4 on H. pylori infections of the stomach tissue in C57BL/6 mice. Methods In this study, 40 specific-pathogen-free female C57BL/6 mice were randomly divided into five groups, namely, the control, ZFM4 pretreatment) ZFM4 pretreatment before H. pylori infected), model (H. pylori infected), triple therapy (H. pylori infected and treated with triple therapy), and ZFM4 treatment groups (H. pylori infected and treated with ZFM4). The preventive and therapeutic effects of Lactobacillus plantarum ZFM4 were evaluated in H. pylori-infected C57BL/6 mice by assessing gastric tissue morphology, inflammatory cytokine levels, microbial composition, and microbial diversity. Results Lactobacillus plantarum ZFM4 was able to survive in low gastric pH and play a role in preventing H. pylori infection. This was evident from a reduction in both, the gastric inflammatory response and expression of inflammatory factors caused by H. pylori infection. Lactobacillus plantarum ZFM4 could also inhibit the growth of H. pylori via its beneficial impact on the gastric microbiota. Conclusion Our findings suggest that Lactobacillus plantarum ZFM4 offers superior preventive effects against H. pylori infections when used alone. However, the therapeutic effect on established infections is weaker. Further clinical trials are needed to confirm the specific dosage, duration, and other aspects of administration.